Efektivitas Komunikasi Promosi Melalui Media Sosial Instagram Di Legen Villa Lubuk Minturun - Agustin, Elyichiya; Susanti, Retnaningtyas (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Instagram is a favorite platform for the majority of people who have great opportunities for business people to use it as a medium for disseminating information in forming a company image and as a promotional communication media. Instagram has a standard metric for evaluating the performance of uploaded content, namely the engagement rate. Instagram Legen Villa Lubuk Minturun has an average engagement rate of 1.06%, this number is very small for an account with more than 7.5 thousand followers. Therefore, the effectiveness of promotional communication through Instagram at Legen Villa Lubuk Minturun is studied through six indicators: message recipients, message content, message media, message format, message source and timeliness. The goal is to explore, analyze, and find out directly the problems that exist in the effectiveness of promotional communication through Instagram. The research method uses qualitative research with descriptive methods. Data collection uses interview, observation and documentation techniques. Informants from various parties consisting of Legen Villa managers, communication science experts, and Instagram followers @legenvilla. The results of this study indicate that promotional communication through Instagram at Legen Villa Lubuk Minturun is quite effective. However, Legen Villa's Instagram needs to improve the public interaction aspect to increase the engagement rate, as well as the addition of visual video content.